2019
DOI: 10.1103/physrevlett.122.150605
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic Spin Transport in a Periodically Driven Integrable Quantum System

Abstract: We demonstrate ballistic spin transport of an integrable unitary quantum circuit, which can be understood either as a paradigm of an integrable periodically driven (Floquet) spin chain, or as a Trotterized anisotropic (XXZ) Heisenberg spin-1/2 model. We construct an analytic family of quasi-local conservation laws that break the spin-reversal symmetry and compute a lower bound on the spin Drude weight which is found to be a fractal function of the anisotropy parameter. Extensive numerical simulations of spin t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 38 publications
5
82
0
Order By: Relevance
“…In this view, the full map Φ full τ can be perceived as an 'integrable Trotterrization', closely resembling the integrable Trotterization of the quantum Heisenberg model obtained in [83,84]. Indeed, we will shortly demonstrate in Section 2.6 below that Eqs.…”
Section: Dynamical Mapmentioning
confidence: 69%
“…In this view, the full map Φ full τ can be perceived as an 'integrable Trotterrization', closely resembling the integrable Trotterization of the quantum Heisenberg model obtained in [83,84]. Indeed, we will shortly demonstrate in Section 2.6 below that Eqs.…”
Section: Dynamical Mapmentioning
confidence: 69%
“…Furthermore, it was shown that this family includes both integrable [60][61][62] and non-integrable cases. In particular, it contains a full parameter line of the integrable trotterized XXZ chain 61,62…”
Section: The Dual-unitary Dynamicsmentioning
confidence: 99%
“…To illustrate how persistent oscillations of extensive many-body observables occur, we consider a Floquet driven spin-1/2 chain of even size N ∈ 2N, introduced in Refs. [34,35] as an integrable Trotterization of the anisotropic Heisenberg (XXZ) model. For simplicity we assume that the thermal ensemble corresponds to the infinite-temperature state…”
Section: Driven Heisenberg Chain At Root-of-unity Anisotropiesmentioning
confidence: 99%
“…The lower bounds are derived for autonomous Hamiltonian dynamics as well as for periodically driven (Floquet) systems. We apply our results to a nontrivial example of a many-body Floquet system that breaks the discrete time-translation symmetry, specifically to the integrable Trotterization of the spin-1/2 XXZ model [34,35].…”
Section: Introductionmentioning
confidence: 99%